The readiness of small and micro food industries based on halal requirements in Malaysia: an expert review through Nominal Group Technique - Alkharib Shah, Asiah; Abu Bakar, Elistina; Mustapha, Ramlan (2024)
The purpose of this study is to identify and prioritize the critical requirements for halal compliance from the Malaysian Halal Certification Procedure Manual (Domestic) 2020 and the Malaysian Halal Management System 2020 for small and micro food industries and validate a set of questionnaire items that reflect the level of readiness industry. The research employed a modified Nominal Group Technique (NGT) with seven expert participants. Using the Fudelo Application, experts evaluated and ranked items related to halal certification requirements with items achieving 100% consensus being the most suitable for inclusion in the questionnaire. The study developed and validated items to assess halal compliance readiness among Malaysia's small and micro food industries. Among the 79 items evaluated, 35 achieved full consensus from seven experts. The findings underscore the importance of raw material control, employee management, cleanliness of processing areas, premises and facilities, records and documentation, equipment maintenance, packaging, and labeling standards, the effectiveness of internal halal control systems, and storage as critical elements reflecting halal compliance readiness in small-scale operations. The study emphasizes the important halal compliance requirements for small and micro food industries in Malaysia. This will help them allocate resources effectively and meet halal standards. In addition, stakeholders, including entrepreneur development agencies, can use this prioritized list to create targeted interventions and support programs. Ultimately, this will enhance the overall readiness and sustainability of halal certification in the industry. This study uniquely identifies and prioritizes halal compliance requirements for Malaysia's small and micro food industries, validates a questionnaire for industry readiness, and evaluates industry readiness based on expert consensus.